The role of audit committee characteristics and I.C. performance on I.C. disclosure: Evidence from the Indonesian banking sector - Wisnu Mawardi; Harjum Muharam; Mulyo Haryanto (Economies, 2023)
This study aims to analyze the influence of audit committee characteristics and intellectual capital performance on intellectual capital disclosure. Characteristics of the audit used in this research are the size of the audit committee, the Number of audit committee meetings, and the financial expertise of the audit committee. The population in this study is a financial services company listed on the Indonesia Stock Exchange in 2019-2021 and collected a sample of 91 companies using the purposive sampling technique. The analysis method used in this research is multiple linear regression using the software SPSS 20. The test result of this study shows that an audit committee or several audit committees positively affect intellectual capital disclosure. However, at the same time, the financial expertise of the audit committee and intellectual capital performance does not affect intellectual capital disclosure.
Keywords: G32; M14; M42; 330; audit committee; intellectual capital disclosure; intellectual capital performance